CALPHAD and the materials genome A 10 year anniversary. (March 2023) - Ågren, John
Abstract: The materials genome initiative was announced by US President Obama 2011. Its actual meaning was initially rather unclear and it seemed as it could contain everything. Nevertheless, in their Scripta paper 2014 Kaufman and Ågren argued that the materials genome, analogously with biological genomes, should be defined as a set of information (databases) allowing prediction of materials structure as well as its response to processing and usage conditions. It thus seemed natural that CALPHAD thermodynamics and kinetics should play an essential role. In the present paper the role of CALPHAD as a way of processing different kind of materials data will be emphasized. The extension from thermochemistry to other properties, industrial applications and extrapolation far from equilibrium will be reviewed.